Factors influence private sector status of loan repayment using logistic regression: A case study of Bank Rakyat on september 2014 / Nur Farah Amira Zahid Shah - Zahid Shah, Nur Farah Amira (Bachelor of Science (Hons.) Statistics, 2015)
This research focused on personal loan for Private Sector employees. A personal loan is an unsecured loan, meaning the borrower does not put up any collateral or security to guarantee the repayment of the loan. There are 1455 customers involved in this study by using secondary data source that was obtained from all Bank Rakyat branch data base system. The researcher interested to determine the association between status of loan repayment and demographic profile of Private Sector employees. Besides that, researcher also interested to identify the main factors that affecting the status of customers loan. Binary logistic regression analysis is used to achieve the objective of this study. Logistic regression is a powerful statistical way of modeling a binomial outcome with one or more explanatory variables. The data were analyzes by using Statistical Package for Social Science (SPSS). The results of Chi-Square contingency table analysis and independent sample t-test show a significantly association between genders, types of repayment and length of service with status ofloan repayment. Furthermore, forward and backward selections were used for this study indicate that the length of service, gender and types of repayment were significant to the model. This research may help Bank Rakyat to reduce the monthly in arrears and nonperforming loan among Private Sector employees